IMPLEMENTATION OF PDRI DURING FRONT-END PLANNING: A STRATEGY TO IMPROVE INDONESIA’S MARITIME INFRASTRUCTURE PROJECT PERFORMANCE - Seng Hansen (OISAA, 2018)
In recent years, Indonesia has heavily invested in infrastructure development. With the aspiration to become a Global Maritime Fulcrum, Indonesia needs to provide maritime infrastructure such as national and international ports and their facilities to support the realization of this aspiration. This certainly requires adequate project planning so that resources and investments can be optimally utilized. That is why a good front-end planning is required so that proposed maritime infrastructure projects can be well selected. One important process of front-end planning is project scope definition where a project is clearly defined and prepared for execution. This paper provides examples of failed/cancelled maritime infrastructure projects due to poor front-end planning. It also provides an idea to implement Project Definition Rating Index (PDRI) as a powerful tool to ensure the fulfillment of project scope definition. The author presents the importance of front-end planning, where the final project investment decision is being made, and explains some steps in implementing the PDRI for maritime infrastructure projects. Thus, this paper contributes in introducing the importance of front-end planning and the usage of PDRI in Indonesia especially for maritime projects so that it may enhance the overall maritime infrastructure project performance.